EFEKTIVITAS PENGGUNAAN ANGGARAN PENDAPATAN BELANJA DESA (APBDes) TAHUN 2015 DI DESA PULAU SENGKILO KECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU - Mauliyanna M. Amin; Zaili Rusli SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aims to determine the Effectiveness of Revenue Budget Expenditure Belanjd Village (APBDes) Year 2015 In Sengkilo Island Village District Kelayang Indragiri Hulu. The theory concepts that researchers use are organizational effectiveness by using Gibson's theory by looking at Clarity of purpose to be achieved, Clarity of goal achievement strategy, Mature Planning, Preparation of appropriate program, and System of supervision and control that educate. The research method used is qualitative research with descriptive data assessment. In data collection, the researcher uses interview, observation, and documentation technique based on Purposive sampling.From the research results show that the Effectiveness of the Use of Revenue Expenditure Budget Village (APBDes) Year 2015 In the Village District Kelayang Indragiri Hulu not effective it appears there are shortcomings, there are many facilities and infrastructure that is not good and there are many programs of community empowerment and development that has not run . The factors that affect the Effectiveness of the Use of Revenue Expenditure Budget Village (APBDes) Year 2015 In the Village of Sengkilo Island Kelayang Sub-district Indragiri Hulu Regency is the Quality of Human Resources and Coordination that has not been good.Keywords: Effectiveness, Implementation, Budget of Village Expenditure (APBDes)